Prohibition of Sexual Enjoyment from a Minor Wife Based on Rational Specification (Mukhassis Lobbiy) - Fatemeh Monazzami; Mahdi Movahedi Moheb (مطالعات فقه و حقوق اسلامی)
The marriage of minors intersects both the domain of marriage and children’s rights, necessitating heightened scrutiny. In cases of minor marriage, while there is a consensus on the prohibition of sexual intercourse, non-coital sexual acts such as tafkhidh (thighing), kissing, and others, even with an infant, have been deemed permissible, despite potentially constituting child abuse. This paper, adopting a descriptive-analytical approach, examines the relevant opinions and their justifications, arguing that sexual enjoyment pertains fundamentally to a mature wife, not a child. Moreover, in addition to the psychological and developmental harms inflicted on the child, which are prohibited under the principle of la darar (prohibition of harm), reason unequivocally condemns such actions. Consequently, these types of non-coital sexual activities are excluded from the permissive ruling by rational specification (mukhassis labbiy) and revert to their primary ruling of prohibition.  Although some scholars have deemed minor marriage entirely invalid to avoid the aforementioned harms, this paper contends that such a marriage may be valid if it serves a rational purpose; otherwise, it should be invalidated. According to general principles of transactions and marriage, the contract remains valid if these conditions are observed. The primary objective of this study, which represents a novel and exclusive contribution, is the application of mukhassis labbiy to resolve a significant legal and jurisprudential issue (the examination of non-coital sexual acts involving a minor wife). While this discussion has traditionally appeared in jurisprudential texts in the form of simplified examples, it has rarely been invoked explicitly in legal rulings (fatwas).